Pedagogical Lessons From Teaching Telehealth via Online Modes: A Systematic Review - Hsien-Jin Teoh; Haruka Kitamura; Sisira Edirippulige (Australian Journal of Clinical Education, 2026)
Interest in telehealth has led to an increase in the availability of online telehealth courses. Understanding student perspectives of the learning experience and how the courses equip students with the skills for their future professions is warranted. To this end, five health, education, and social science electronic databases and a search engine (i.e., Pubmed, EBSCO, Proquest, Elsevier, and Google Scholar) were searched as part of a systematic review for peer-reviewed research published in English over 10 years (2013-2023). Ten studies were selected for the final review, resulting in the perspectives of 2,305 healthcare students and professionals. The curriculum content and student feedback were synthesised using thematic analyses and presented using a combination of flowcharts and tables. Each study was also assessed for bias using critical appraisal tools for qualitative, quantitative and mixed-method research designs. Key pedagogical themes emerged, including simulations, interprofessional collaboration, resources, self-directed learning, peer learning, feedback, and technology. The use of simulations and interprofessional collaboration emerged as the two most regularly cited aspects of teaching that students found useful. Recommendations described potential inclusion of pedagogical techniques when conducting online training, and teaching methodology requiring further investigation.